HEART RATE VARIABILITY PARAMETERS IN PATIENTS WITH ARTERIAL HYPERTENSION IN DEPENDENCE ON THE TYPE OF DAILY BLOOD PRESSURE PROFILE - Gorantla, S. G. B. K.; Petrenko, O. V.; Martynenko, O. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2017)
Violation of functioning of the autonomic nervous system is an important factor in the formation and progression of arterial hypertension (AH). Abnormal nocturnal blood pressure (BP) reduction is regarded as an independent prognostic factor for cardiovascular complications in patients with AH. One of the possible factors that determine the violation of BP circadian rhythm can be imbalance of different parts of autonomic nervous system. The aim of our study was to study heart rate variability (HRV) in patients with AH, dependently of BP profile. 72 patients with AH were examined. Average age was 57 ± 11 years. All patients underwent ambulatory BP (ABPM) and ECG monitoring. To define the daily profile the nocturnal BP dip was quantified and for HRV evaluation the frequency analysis method was used. HRV changes in patients with AH present with reduced total power and with a violation in the ratio of the powers of very low, low and high frequencies, enhanced sympathycotension and influence of humoral factors. Violations of systolic BP (SBP) daily profile was mainly characterized by an increase in the power of low frequency waves, which indicates an intensification of sympathetic and decreased parasympathetic influences. Violations of diastolic BP (DBP) daily profile were mainly characterized by a relative increase in the power of very low frequency waves. The obtained results showed that in the management of patients with AH it is important not only to control the circadian SBP and DBP profiles, but the evaluation of HRV also.